How to optimize HCV therapy in genotype 2 patients. (3rd January 2013) - Grassi, Eleonora; Aghemo, Alessio
Abstract: Hepatitis C Virus (HCV) Genotype 2 accounts for 10% of the patients with chronic HCV worldwide. The current standard of care (SOC) in these patients is 24 weeks of Pegylated Interferon (PEG‐IFN) plus Ribavirin (RBV), with sustained virological response rates (SVR) of 80–90%. However, there are subgroups of patients with HCV‐2, such as those with advanced fibrosis/cirrhosis, in whom SVR rates are still suboptimal, and highly responsive groups in whom SVR rates reach 95%. Treatment optimization is necessary to maximize efficacy in the former group and reduce treatment‐related side effects in the latter. Unfortunately, any attempt to modify the duration or dosing of the SOC according to baseline factors has been disappointing and should not be continued at present. On the other hand on‐treatment HCV RNA kinetics are fundamental for individualized treatment regimens because achieving negative HCV RNA at week 4 (rapid virological response, RVR) is the key factor when the duration of PEG‐IFN/RBV is tailored in HCV‐2 patients. Several studies have shown that treatment can be shortened to 16 weeks in HCV‐2 patients with a RVR, without increasing the risk of post‐treatment relapse, thus increasing tolerance to treatment while reducing healthcare costs. On the other hand, patients who do not achieve a RVR correspond to a population of difficult‐to‐cure HCV‐2 patients who need alternative treatment strategies which are not yet available.